Work Environment, Work Conflict, and Employee Performance: A Literature Review - Nourman Adittya, Helmi; Rivai Zainal, Veithzal; Hakim, Azis (International Journal of Advanced Multidisciplinary, 2023)
The aim of this paper is to provide a structured literature review on the constructs of work environment, work conflict, employee performance, and empirical evidence on the relationship between work environment, work conflict, and employee performance in Indonesia context. 24 (twenty four) papers published during 2018-2022 that investigates work environment, work conflict, employee performance, and the relationship between work environment, work conflict, employee performance were reviewed. The results of the literature review regarding the effect of the work environment on employee performance show different results. The majority (83.33%) indicated that the work environment has a positive and significant effect on employee performance, while the remaining (16.67%) indicated that the work environment has insignificant effect on employee performance. The effect of work conflict on employee performance also shows different results. The majority (91.67%) indicated that work conflict has a significant effect on employee performance and the remaining (8.33%) indicated that work conflict has insignificant effect on employee performance. Of all the empirical results showing that work conflict has a significant effect on employee performance, it is obtained evidence that 54.54% has a positive effect, while 45.46% has a negative effect. For this reason, it is recommended that organizations 1) create a work environment (both physical and non-physical) that is conducive to improving employee performance; 2) manage conflicts that occur in the workplace effectively.